Meningkatkan Niat Beli Konsumen Melalui Pemasaran Digital: Iklan, Celebrity, Dan Influencer - Wiraputra, Ardina Lukita; Irwansyah, Irwansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study investigates the impact of various digital marketing strategies, such as advertising, celebrity endorsements, and influencer marketing, on customer purchase intentions within the cosmetics sector, specifically focusing on the Scarlett brand in Indonesia. In the contemporary digital landscape, characterized by heightened rivalry, it is imperative to comprehend the optimal marketing methods employed on social media platforms. The present study employs a quantitative methodology. Data is generated from 384 respondents through the utilization of a questionnaire. The findings derived from the regression analysis demonstrate that each marketing approach exhibits a favorable influence on consumer purchase intentions within the context of Instagram. Celebrity endorsements have the most significant impact, then advertising and influencer marketing. The psychological impact of celebrities who enjoy high regard among fans can help to explain the significant impact of celebrity endorsements. The efficacy of social media advertising in enhancing customer awareness of brands and products has been well documented. Although influencer marketing has been found to have a favorable impact, its influence appears to be somewhat less important. This study offers significant insights for organizations in the process of choosing the most efficient digital marketing methods to augment consumer buy intent on the Instagram platform. Nevertheless, it is important to acknowledge the limits of this study, particularly its narrow focus on the cosmetics business in Indonesia. Future research endeavors should aim to explore variances in social media platforms and expand the geographic coverage to provide a more comprehensive understanding of the topic.